Orofacial clefts and congenital heart disease: is there a relationship? (Research, Society and Development, 2022)
Orofacial clefts are congenital craniofacial deformities commonly seen in children, especially cleft lip and palate, may be caused by environmental, genetic or unknown factors. These pathologies can occur together with other embryonic malformations, with congenital heart diseases being one of the most common. This study aimed to carry out an integrative review of the literature on the relationship between orofacial clefts and congenital heart disease (CHD), verifying the main risk factors addressed in the literature and the prevalence of these anomalies together. For the survey of articles in the literature, a search was carried out in the following databases: Google Scholar, Pubmed and Scielo. The following descriptors and their combinations in Portuguese and English were used to search for articles: "cleft palate", "cleft palate associated with congenital heart disease", "prevalence of cleft palate", "orofacial clefts" and the same translated terms for the English language. Data analysis showed that males are the most affected by orofacial clefts (55.1%), with cleft lip and palate being the most prevalent type (52.72%). Regarding CC, they are present in up to 16.57% of patients with orofacial clefts. It is concluded, therefore, that CC may be associated with orofacial clefts, although this occurs in a minority of cases. A possible explanation for this fact is the position in which the fetus develops in the mother's womb, since during the period of embryogenesis there is a proximity between the face and the thorax.